2006
DOI: 10.1055/s-2005-858867
|View full text |Cite
|
Sign up to set email alerts
|

Funktionelle Ergebnisse nach Intraokularlinsenimplantation mit oder ohne Blaulichtfilter: ein intraindividueller Vergleich bei 14 Kataraktpatienten

Abstract: This intraindividual comparison revealed no relevant differences concerning mesopic contrast sensitivity and the subjective visual perception after implantation of one IOL with or without a blue light filter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
9
1
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 17 publications
1
9
1
3
Order By: Relevance
“…Another clinical trial of fewer patients found that 2 of 13 patients with blue-light-filtering IOLs reported slightly yellow color vision at the first postoperative day that resolved in 1 patient after 4 weeks. 15 Similar observations were reported in 1 of 5 patients by Olson and Miller,22 although there were no complaints about color vision 6 months after surgery in this small patient group.…”
Section: Complicationssupporting
confidence: 74%
See 1 more Smart Citation
“…Another clinical trial of fewer patients found that 2 of 13 patients with blue-light-filtering IOLs reported slightly yellow color vision at the first postoperative day that resolved in 1 patient after 4 weeks. 15 Similar observations were reported in 1 of 5 patients by Olson and Miller,22 although there were no complaints about color vision 6 months after surgery in this small patient group.…”
Section: Complicationssupporting
confidence: 74%
“…Although some authors express concern about impaired scotopic sensitivity, 5,12,13 clinical investigations have not found decreased contrast sensitivity in eyes with yellowtinted IOLs. 3,11,14,15 In a study of contrast sensitivity in diabetic patients, Rodríguez-Galietero et al 16 found better contrast sensitivity values in eyes with an AcrySof Natural. This corresponds to results in previous studies that report that the use of yellow filters by healthy phakic patients improve image contrast and thus contrast sensitivity.…”
Section: Complicationsmentioning
confidence: 97%
“…Accumulating evidence suggests that performance in subjective visual tests, specifically contrast sensitivity and color perception, is slightly affected or not affected by blue-light filtering. [5][6][7][8][9][10][11][12][13] However, because these psychophysical studies tap the system at its output stage, the effects of filters on the underlying neural activity might be obscured by compensatory mechanisms along the processing chain in the visual pathways. It would, therefore, be beneficial to clarify whether neural signals close to the input stage are affected by filter-related changes in the spectral composition of the visual stimuli.…”
mentioning
confidence: 98%
“…1,4,24,25 Although there are anecdotal data available to support these assumptions, the majority of scientific findings on yellow-tinted blue light-filtering IOLs show no clinically significant differences in visual performance under natural lightning conditions compared with conventional UV light-filtering IOLs. 19,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] Commercially available and previously studied blue light-filtering IOLs are mainly equipped with yellow-tinted chromophores. In contrast, Ophtec BV has developed a different type of blue light-filtering IOL, the Oculaid PC 440 Y Orange Series IOL, which is covalently bound with an orange chromophore.…”
mentioning
confidence: 99%